Room2Room: Enabling Life-Size Telepresence in a Projected Augmented Reality Environment - Pejsa, Tomislav; Kantor, Julian; Benko, Hrvoje; Ofek, Eyal; Wilson, Andy (CSCW '16 Proceedings of the 19th ACM Conference on Computer-Supported Cooperative Work & Social Computing, 2016)
Best Paper CSCW 2016 Room2Room is a telepresence system that leverages projected augmented reality to enable life-size, co-present interaction between two remote participants. Our solution recreates the experience of a face-to-face conversation by performing 3D capture of the local user with color + depth cameras and projecting their life-size virtual copy into the remote space. This creates an illusion of the remote person’s physical presence in the local space, as well as a shared understanding of verbal and non-verbal cues (e.g., gaze, pointing.) In addition to the technical details of two prototype implementations, we contribute strategies for projecting remote participants onto physically plausible locations, such that they form a natural and consistent conversational formation with the local participant. We also present observations and feedback from an evaluation with 7 pairs of participants on the usability of our solution for solving a collaborative, physical task. https://www.youtube.com/watch?v=2o6krhxpUGk